Insect herbivory on seedlings of rainforest trees: Effects of density and distance of conspecific and heterospecific neighbours - Downey, H; Lewis, O; Bonsall, M; Fernandez, D; Gripenberg, S (Wiley, 2018)
Natural enemies of plants such as insect herbivores can contribute to structuring and maintaining plant diversity in tropical forests. Most research in this area has focused on the role of specialized enemies and the extent to which herbivory on individual plant species is density‐dependent. Relatively few insect herbivores specialize on a single host plant species. Insect herbivores that feed on more than one plant species may link the regeneration dynamics of their host species through “apparent competition” or “apparent mutualism.” We investigated herbivory and survival of seedlings of two tropical tree species (Cordia alliodora and Cordia bicolor) in the forests of Barro Colorado Island (Panama). We used experiments and observations to assess seedling fate in relation to the presence of conspecifics and heterospecifics across a range of spatial scales. Herbivory significantly increased seedling mortality and was highest at high local densities of C. alliodora seedlings. There was also evidence that high local densities of C. alliodora increased herbivory on co‐occurring C. bicolor seedlings. Synthesis. The elevated rates of seedling herbivory at high densities of conspecifics documented in our study are consistent with the predictions of the Janzen–Connell hypothesis, which explains how so many plant species can coexist in tropical forests. Our data also highlight the possibility that herbivore‐mediated density‐dependence, facilitated by herbivores that feed on multiple plant species, can also occur across plant species. Enemy‐mediated indirect effects of this sort have the potential to structure plant communities.